The Myotendinous Junction—A Vulnerable Companion in Sports. A Narrative Review - Jakobsen, Jens Rithamer; Krogsgaard, Michael Rindom (Frontiers in Physiology, 2021)
The incidence of strain injuries continues to be high in many popular sports, especially hamstring strain injuries in football, despite a documented important effect of eccentric exercise to prevent strains. Studies investigating the anatomical properties of these injuries in humans are sparse. The majority of strains are seen at the interface between muscle fibers and tendon: the myotendinous junction (MTJ). It has a unique morphology with a highly folded muscle membrane filled with invaginations of collagen fibrils from the tendon leading to an increased area of force transmission between muscle and tendon. There is a very high metabolism in the muscle cells approaching the MTJ, but little is known about how it adapts to exercise and which structural changes heavy eccentric exercise may introduce. This review summarizes the current knowledge about the anatomy, composition and adaptability of this structure, and discusses potential reasons why strain injuries can be prevented by eccentric exercise.